Electrochemical oxidation mechanisms for selective products due to C–O and C–C cleavages of β-O-4 linkages in lignin model compounds. Issue 20 (12th May 2020) - Chen, Jing; Yang, Hanling; Fu, Hongquan; He, Hongyan; Zeng, Qiang; Li, Xuehui
Abstract : This work may provide an idea for the study of the mechanism of lignin electrocatalytic oxidation with a selective distribution of depolymerization products. Abstract : Electrochemical oxidation is a promising and effective method for lignin depolymerization owing to its selective oxidation capacity and environmental friendliness. Herein, the electrooxidation of non-phenolic alkyl aryl ether monomers and β-O-4 dimers was experimentally (by cyclic voltammetry, in situ spectroelectrochemistry, and gas chromatography-mass spectroscopy) and theoretically (by DFT calculations) explored in detail. Compared to the reported literature (T. Shiraishi, T. Takano, H. Kamitakahara and F. Nakatsubo, Holzforschung, 2012, 66 (3), 303–309), 1-(4-ethoxyphenyl)ethanol showed a distinguishable oxidation pathway, where the resulting carbonyl product surprisingly underwent a bond cleavage on alkyl–aryl ether to ultimately produce a quinoid like compound. In contrast, β-O-4 dimers, like 2-phenoxy-1-phenethanol and 2-phenoxyacetophenone also demonstrated electrochemical oxidation induced by Cβ –O and Cα –Cβ bond cleavages. For the oxidation products, the presence of the Cα -hydroxyl group in dimers was the key to selectively generate aldehyde-containing species under mild electrochemical conditions, otherwise it produces alcohol-containing products following a different mechanism compared to the Cα O containing dimers.